Voting technology the not-so-simple act of casting a ballot - Herrnson, Paul S., 1958-; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2008)
"Evaluates five commercially available voting systems, against different criteria (including ease of use, speed, and accuracy) using field and laboratory experiments and expert reviews. Initiates new research into interactions between ballot format and voter behavior. Offers best practices for voting system manufacturers, ballot designers, election officials, political observers, and voters"--Provided by publisher.
The study of electronic voting -- A new generation of voting systems -- Voter reactions to electronic voting systems -- The accuracy of electronic voting systems -- Inequality in the voting booth -- Vote verification systems -- Toward more user-friendly voting and election systems.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Electronic voting -- United States; Voting -- Technological innovations; Voting-machines -- United States -- Reliability; Elections -- United States -- Equipment and supplies; Electronic books